Romiplostim for chemotherapy‐induced thrombocytopenia: Efficacy and safety of extended use. Issue 3 (10th May 2022) - Wilkins, Cy R.; Ortiz, Jocelyn; Gilbert, Leah J.; Yin, Shen; Mones, Jodi V.; Parameswaran, Rekha; Mantha, Simon; Soff, Gerald A.
Abstract: Background: Chemotherapy‐induced thrombocytopenia (CIT) is common during treatment with antineoplastic therapies and may adversely impact chemotherapy dose intensity. There is no approved therapy for CIT. In our recent phase II randomized study, romiplostim led to correction of platelet counts in 85% of treated patients and allowed resumption of chemotherapy, with low rates of recurrent CIT in the first two cycles or 8 weeks of chemotherapy. However, there is a lack of long‐term data on the efficacy and safety of romiplostim in CIT. Objectives: To analyze efficacy and safety of romiplostim in the patients in the phase 2 study, who received romiplostim for ≥1 year. Patients/Methods: Twenty‐one patients remained on romiplostim for ≥1 year. We analyzed the effect of romiplostim on platelet counts, absolute neutrophil counts, and hemoglobin, as well as impact on ongoing chemotherapy. We also tracked venous or arterial thrombotic events. Results: During the study period, romiplostim was effective in preventing reduction of chemotherapy dose intensity due to CIT. Fourteen of the 20 (70%) analyzable patients experienced no episode of CIT, 4 subjects experienced a single chemotherapy dose delay due CIT, and 2 patients required a chemotherapy dose reduction. Platelet counts were preserved throughout the duration of the extension analysis. One patient experienced a proximal deep vein thrombosis, and one patient experienced multiple tumor‐related ischemic events. Conclusions: Long‐term use of romiplostim for treatment of CIT was effective and safe, with no evidence of resistance or increased risk of thrombosis.